Fatty Acid Taste Receptor GPR120 Activation by Arachidonic Acid, Eicosapentaenoic Acid, and Docosahexaenoic Acid in Chickens - Fuminori Kawabata; Yuta Yoshida; Seiga Kuba; Yuko Kawabata; Shotaro Nishimura; Shoji Tabata (The Journal of Poultry Science, 2022)
It has been reported that the supplementation of chicken diet with polyunsaturated fatty acids (PUFAs) such as arachidonic acid (AA), eicosapentaenoic acid (EPA), or docosahexaenoic acid (DHA) affects the qualities of eggs and meat. Previous studies have shown that a functional fatty acid taste receptor, G protein-coupled receptor 120 (GPR120), is broadly expressed in chicken oral and gastrointestinal tissues, and chickens have a gustatory perception of oleic acid, which is a chicken GPR120 agonist. The aim of this study was to elucidate the role of chicken GPR120 in response to PUFAs in chicken diets. Ca2+ imaging analyses revealed that chicken GPR120 was activated by AA, EPA, and DHA in a concentration-dependent manner. These results suggest that chickens can detect PUFAs via GPR120 in the oral and gastrointestinal tissues, implying that chickens have a gustatory perception of PUFAs.